F|Heat: A GIS-based compliance tool for municipal heat planning in Germany - Sommer, Philipp; Willenbrink, Hinnerk; Goray, Lars; Scheffler, Mark; Brügging, Elmar (International Journal of Sustainable Energy Planning and Management, 2026)
Municipal heat planning is becoming a mandatory element of local climate policy in Germany, yet many smaller municipalities lack geospatial tools that are transparent, reproducible and aligned with the German Heat Planning Act (WPG). This paper presents F|Heat, an open-source QGIS extension that supports early-stage municipal heat planning by automating data acquisition, building-level heat-demand preparation, heat-density and heat-line-density analyses, preliminary district-heating network routing, pipe dimensioning, heat-loss estimation and load-profile generation. The method is demonstrated for a district in Barntrup, North Rhine-Westphalia, Germany. The case study connects 268 buildings with an annual heat demand of 11.9 GWh and generates a 9.1 km preliminary network. Simulated annual heat losses amount to 1.6 GWh with standard insulation and 1.4 GWh with enhanced insulation. Using DN-specific network investment assumptions, the annualised network cost contribution is estimated at 0.042 EUR·kWh-1. The results show that F|Heat can provide a reproducible GIS-based workflow for suitability assessment, status-quo analysis and preliminary district-heating area assessment. The tool does not replace detailed techno-economic optimisation, heat-source assessment or engineering design, but narrows the gap between statutory heat planning requirements and the data-processing capacity of municipalities.